TECHNICAL PARAMETERS AND ENERGY EFFICIENCY OF AN OIL SLUDGE PROCESSING UNIT - Nuritdinov, Azimjon; Abdullaev, Olim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents information on units designed for processing oil sludge generated during oil and gas processing operations, characterized by a high content of water and mineral impurities. The operating temperature regimes, structural parameters and energy efficiency of the unit are analyzed. Experimental results demonstrate that the implementation of an economizer and a preheating system reduces fuel consumption by 15–20% while increasing the yield of light fractions by 10–12%. As a result of the processing, technological fuels and bitumen are obtained, confirming their potential application in the construction and fuel industries.